A data driven dispatcher for big data applications in heterogeneous systems - Souza Junior, Paulo Ricardo Rodrigues de (2018)
Mankind is increasing technology capacity every day, as it is taking place in multiple areas like automation, predicting, making actions, and so on. In this process, data is produced in different ratios and quantities, and from a close point of view the data production of a single sensor is not much and does not provide clear insights. However, a global vision and the union of that information may contain helpful knowledge about business intelligence, people and sensor behavior. The global view of all this data is called Big Data and may achieve overwhelming amounts of data, which is being produced in outstanding rates by devices and people. Therefore, it is necessary to provide solutions to manage Big Data systems, which give robustness and quality of service. In order to achieve robust systems to process high amounts of data, Big Data frameworks are proposed and deployed using several management tools. Furthermore, Big Data frameworks are usually separated in different perspectives of processing (i.e., batch and stream processing), and focuses on processing balanced data in homogeneous environments. Stream and Batch Processing Engines have to support high data ingestion to ensure the quality and efficiency for the end-user or a system administrator. The data flow processed by SPE fluctuates over time and requires real-time or near real-time resource pool adjustments (network, memory, CPU and other). This scenario leads to the problem known as skewed data production caused by the non-uniform incoming flow at specific points on the environment, resulting in slow down of applications produced by network bottlenecks and inefficient load balance. The current proposal of this thesis is the Aten a data-driven dispatcher as a solution to overcome unbalanced data flows processed by Big Data Stream applications in heterogeneous systems. Aten manages data aggregation and data streams within message queues, assuming different algorithms as strategies to partition data flow over all the available computational resources. The thesis presents results indicating that is possible to maximize the throughput and also provide low latency levels for SPEs.